The Translation of Foreign Novels into Malay by Dewan Bahasa dan Pustaka: (Penterjemahan Novel Bahasa Asing ke dalam Bahasa Melayu oleh Dewan Bahasa dan Pustaka) (Malay Literature, 2015)
Established in 1956 with the main purpose of developing the Malay language, Dewan Bahasa dan Pustaka (DBP) has also played a pivotal role in the translation of foreign works into Malay. Very little, however, has been studied in terms of its contribution to the development of translation activities in Malaysia. This paper aims to provide an overview of the translation of foreign novels into Malay by DBP from the time of its inception. A survey was carried out for this purpose. The results show that a total of 72 foreign novels have been translated into Malay and published by DBP. The study was also able to determine specific trends in the translation of foreign novels by DBP. Although limited in scope, this study is believed to be important as it is able to contribute to existing discourse on the history of translation in Malaysia.Keywords: translation, Dewan Bahasa dan Pustaka, publishing, novels, translation history